Distributional impacts of the rice tariffication in the Philippines - Balié, Jean; Minot, Nicholas; Valera, Harold Glenn (Economic Society of Australia, 2021)
In March 2019, the government of the Philippines promulgated a bill called the Rice Tariffication Law (RTL). It has dramatically changed the policy landscape in the rice sector and generated heated debates on how it would affect food security and poverty. This study explores the welfare effects of this reform across different types of households. We rely on the IRRI Global Rice Model to simulate the domestic price effects of the reform (Balié and Valera, 2020) and the Family Income and Expenditure Survey (FIES) to study the welfare impact of these price changes. Our results show that the RTL reduces consumer and producer rice prices, which affects households on the production and the consumption sides. Because a large majority of households are net buyers of rice and the policy reform reduces rice prices, most households benefit from the reform. Overall, the effects of the reform on poverty are beneficial. The poorest quintiles are positively affected, while the richest quintiles are unaffected or slightly worse-off. Spatially, the poorest regions also benefit the most. However, the rice growers who are net sellers are negatively impacted. The government should seek to mitigate the negative effects on non-competitive rice growers. Investments in public goods and services are a promising option to ease the emergence of on-farm and off-farm businesses as more profitable alternatives to rice production.